Impact of the donor structure in new D–π–A systems based on indolo[3, 2, 1-jk]carbazoles on their thermal, electrochemical, optoelectronic and luminescence properties. Issue 23 (25th May 2021) - Szafraniec-Gorol, Grażyna; Slodek, Aneta; Zych, Dawid; Vasylieva, Marharyta; Siwy, Mariola; Sulowska, Karolina; Maćkowski, Sebastian; Taydakov, Ilya; Goriachiy, Dmitry; Schab-Balcerzak, Ewa
Abstract : New D–π–A fluorophores based on indolo[3, 2, 1- jk ]carbazole (ICz) were synthesized and thoroughly investigated, where the ICz framework is connected by an ethylene bridge with various donor moieties. Abstract : In this work, novel fluorophores with D–π–A architectures (ICz-1–ICz-6 ) were synthesized and investigated, where the indolo[3, 2, 1- jk ]carbazole (ICz) framework is connected by an ethylene bridge with extensive donor moieties – e.g., fluorene, carbazole, phenothiazine, methoxyphenyl, bithiophene, and dibenzothiophene. The influences of the donor character of the substituents in the indolocarbazole derivatives on their thermal, optical and electrochemical properties were explored and compared with the quantum chemical calculations based on DFT and TD-DFT. All ICz-1–ICz-6 compounds emit blue light with emission peaks between 390 and 430 nm in solution, except for compound ICz-5 with a strong phenothiazine donor, which emits light at 463 nm. The ICz-6 derivative with the dibenzothiophene unit features an exception to Kasha's rule. For the selected compounds ICz-2, ICz-4, and ICz-5, preliminary electroluminescence tests were performed, both based on devices with a neat compound (ITO/PEDOT:PSS/ICz/Al) and with a guest–host configuration (ITO/PEDOT:PSS/PVK:PBD:ICz/Al), where two emission bands were detected covering the range from 400 to over 900 nm. Additionally, several multilayer OLED devices (ITO/PEDOT:PSS/poly-TPD/ICz-2–5 /TPBi/LiF/Al) were prepared, and all diodes showed electroluminescence at 570 nm.